Undergraduate Students' Perceptions of Online Learning Post Pandemic Covid-19 - Maman Suherman; Cece Hidayat; Lilis Suwandari; Emay Mastiani; Ruswandi, Agus (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
After the COVID-19 pandemic. network-based learning has become a necessity and habit for many universities in Indonesia. This research focuses on the problem of student's lack of participation in online learning through virtual meetings. The purpose of this study is to analyze undergraduate students' perceptions of online lectures. This study used a quantitative approach with a survey method. involving 233 students from the Faculty of Teacher Training and Education as respondents. The data collection method used was a questionnaire with an instrument in the form of a questionnaire sheet. After the data was collected. it was analyzed using the descriptive statistical analysis method. Based on the findings of this study. students' perceptions of online learning overall are at a high level. especially on the aspect of flexibility. which is rated very positively. However. some aspects need more attention. primarily related to the effectiveness of online learning in improving academic achievement and reducing boredom. It can be concluded that while students appreciate the flexibility and convenience of online learning. there is a need to improve the quality of the learning process to make it more effective and meaningful for students. The implication is that universities need to develop more interactive. meaningful and engaging online learning strategies to increase student participation. In addition. more varied types of assignments and the use of technology that supports more collaboration will increase the effectiveness and satisfaction of online learning in the future.